DIFFERENCE IN DEGREE OF SUB-LETHAL DAMAGE RECOVERY BETWEEN CLINICAL PROTON BEAMS AND X-RAYS. Issue 1 (20th December 2018) - Matsumoto, Yoshitaka; Ando, Koichi; Kato, Takamitsu A; Sekino, Yuta; Ishikawa, Hitoshi; Sakae, Takeji; Tsuboi, Koji; Sakurai, Hideyuki
Abstract: Fractionated proton beam radiotherapy is spreading worldwide these days. However, biological data of sub-lethal damage recovery (SLDR) after proton irradiation is not known yet. We here conducted split-dose experiments (20–360 min intervals) to clarify SLDR kinetics, and also compared the kinetics between cells with different repairability of DNA double-strand breaks. CHO and 51D1 cell lines but not V3 cell line showed significant SLDR, which reached plateau in 4–6 h. The recovery rates and recovery halftime of SLDR after X-rays were significantly higher and shorter than proton beams for CHO and 51D1 cells, respectively. Additionally, the frequency of remaining gamma-H2AX foci after two fractions was remarkably higher for X-rays than proton beams. These data suggest that there is a difference between proton beam and X-rays in SLDR and the retained DNA double-strand breaks after split-dose irradiation.